Preoperative aerobic fitness and perioperative outcomes in patients undergoing cystectomy before and after implementation of a national lockdown - Nicholas Tetlow; Amy Dewar; Pietro Arina; Melanie Tan; Ashwin N. Sridhar; John D. Kelly; Nishkantha Arulkumaran; Robert C.M. Stephens; Daniel S. Martin; Suneetha R. Moonesinghe; John Whittle (BJA Open, 2024)
Background: Lower fitness is a predictor of adverse outcomes after radical cystectomy. Lockdown measures during the COVID-19 pandemic affected daily physical activity. We hypothesised that lockdown during the pandemic was associated with a reduction in preoperative aerobic fitness and an increase in postoperative complications in patients undergoing radical cystectomy. Methods: We reviewed routine preoperative cardiopulmonary exercise testing (CPET) data collected prior to the pandemic (September 2018 to March 2020) and after lockdown (March 2020 to July 2021) in patients undergoing radical cystectomy. Differences in CPET variables, Postoperative Morbidity Survey (POMS) data, and length of hospital stay were compared. Results: We identified 267 patients (85 pre-lockdown and 83 during lockdown) who underwent CPET and radical cystectomy. Patients undergoing radical cystectomy throughout lockdown had lower ventilatory anaerobic threshold (9.0 [7.9–10.9] vs 10.3 [9.1–12.3] ml kg−1 min−1; P=0.0002), peak oxygen uptake (15.5 [12.9–19.1] vs 17.5 [14.4–21.0] ml kg−1 min−1; P=0.015), and higher ventilatory equivalents for carbon dioxide (34.7 [31.4–38.5] vs 33.4 [30.5–36.5]; P=0.030) compared with pre-lockdown. Changes were more pronounced in males and those aged >65 yr. Patients undergoing radical cystectomy throughout lockdown had a higher proportion of day 5 POMS-defined morbidity (89% vs 75%, odds ratio [OR] 2.698, 95% confidence interval [CI] 1.143–6.653; P=0.019), specifically related to pulmonary complications (30% vs 13%, OR 2.900, 95% CI 1.368–6.194; P=0.007) and pain (27% vs 9%, OR 3.471, 95% CI 1.427–7.960; P=0.004), compared with pre-lockdown on univariate analysis. Conclusions: Lockdown measures in response to the COVID-19 pandemic were associated with a reduction in fitness and an increase in postoperative morbidity among patients undergoing radical cystectomy.